Chapter Nitric Oxide: Key Features in Spermatozoa - Staicu, Florentin-Daniel (InTechOpen, 2017)
Several in vitro studies have pointed to the importance of nitric oxide (NO) in the female and male reproductive system in mammals. Its functions vary from preventing oocyte aging, improving the integrity of the microtubular spindle apparatus in aged oocytes, modulating the contraction of the oviduct, to regulating sperm physiology by affecting the motility, inducing chemotaxis in spermatozoa, regulating tyrosine phosphorylation, enhancing the sperm-zona pellucida binding ability, and modulating the acrosomal reaction. In spermatozoa, NO exerts its functions in different ways, which involve key elements such as the soluble isoform of guanylate cyclase, cyclic guanosine monophosphate (cGMP), cyclic adenosine monophosphate (cAMP), protein kinase A (PKA), adenylate cyclase, and the extracellular signal-regulated kinase (ERK) pathway. Furthermore, NO leads to the S-nitrosylation of several sperm proteins, among them a substantial group associated with energy generation and cell movement, but also with signal transduction, suggesting a role for S-nitrosylation in sperm motility and in modulating the sperm function, respectively. In this chapter, an overview of how NO modulates the sperm physiology is presented, based on the knowledge acquired to this day.